Quality of Intermodal Public Transportation Services as a Tool of Economic Efficiency in East Lombok Regency - Fiardi, Andi; Sulfi, Daan; Fuady, Ian; Suradika, Agus; Andriansyah , Andriansyah (Journal of Social and Policy Issues, 2025)
Public transportation supports community mobility and drives economic growth, especially in tourist areas like the East Lombok Regency. This study discusses how the quality of intermodal public transportation services contributes to economic efficiency in the area. Using a descriptive quantitative approach, this study collected data from 109 respondents who used DAMRI intermodal public transportation through a Likert scale-based survey and analyzed using the Weigh Means Score (WMS) method. The study results showed that intermodal public transportation services in East Lombok Regency were rated "Good," with an average score 3.83. The most appreciated aspect was officers' concern for vulnerable group passengers, such as the elderly and disabled, with a score of 3.97. However, several things still need to be improved, especially in integration between modes of transportation. Public transportation also been shown to positively impact the local economy, especially in supporting the tourism sector and creating business opportunities for the surrounding community. This study provides recommendations for local governments to continue to strive to improve infrastructure and transportation systems to make more efficient and affordable services for the community and tourists. The findings serve as a strategic reference for local governments to design more inclusive and economically beneficial public transportation systems.